Effect of Using an Age‐adjusted D‐dimer to Assess for Pulmonary Embolism in Community Emergency Departments. (24th December 2020) - Ghobadi, Ali; Lin, Bryan; Musigdilok, Visanee V.; Park, Stacy J.; Palmer‐Toy, Darryl E.; Gould, Michael K.; Vinson, David R.; Hutchison, Dana M.; Sharp, Adam L.
Abstract: Background: The objective of this study was to evaluate the effect of changing the laboratory‐reported D‐dimer reference intervals to age‐adjusted reference intervals on the use of advanced chest imaging and 30‐day adverse events among emergency department (ED) encounters. Methods: A retrospective interrupted time‐series analysis of ED encounters for patients > 50 years evaluated for suspected pulmonary embolism (PE) from April 2014 to April 2016. The primary outcome was use of advanced diagnostic imaging, and the secondary outcome was 30‐day mortality or PE diagnosis. Secondary analyses also quantified delayed PE diagnoses pre‐ and postintervention. A generalized estimating equation segmented logistic regression model, adjusting for patient and facility characteristics, was used to determine changes in odds of diagnostic imaging and 30‐day mortality or PE diagnoses. Results: A total of 10, 534 (5, 153 pre‐ and 5, 381 postimplementation) ED encounters were included. Advanced imaging was obtained in 35.9% of pre‐ versus 33% of postimplementation encounters. Age‐adjusted D‐dimer (AADD) showed a small and nonsignificant decrease in month‐to‐month trends of advanced chest imaging postimplementation (odds ratio [OR] = 0.98, 95% confidence interval [CI] = 0.96 to 1.00). Use of advanced imaging in patients with D‐dimer values lower than 500 ng/mL fibrinogen‐equivalent units (FEU) was similar in the preintervention (5.8%) and postintervention (6.8%) periods. However, imaging was obtained in 30% of patients postintervention with a D‐dimer result less than AADD reference interval, but more than the historical 500 ng/mL FEU reference interval. Implementing an AADD threshold demonstrated no change in the rate of 30‐day adverse events (missed PE or mortality). Conclusion: Changing the laboratory‐reported D‐dimer reference intervals for evaluation of PE was not associated with reduction in advanced chest imaging and did not increase 30‐day adverse events. However, there was substantial noncompliance with the age‐adjusted reference intervals in the postintervention period likely blunting the impact of this intervention.